Analysis of the Determinants of Families at Risk of Stunting in Ogan Komering Ilir and Lahat Regencies - Ditiaharman, Mutya; Nengyanti, Nengyanti; Sitorus, Rico Januar (Program Pascasarjana Universitas Sriwijaya, 2025)
The prevalence of stunting among children under five in South Sumatra Province decreased from 24.8% in 2021 to 20.3% in 2023. Lahat Regency showed the most significant decline, while Ogan Komering Ilir Regency had the highest prevalence of stunting. This study analyzes determinants of stunting risk in families (KRS) in these regencies. Using secondary data from Perwakilan BKKBN Provinsi Sumatera Selatan, we examined families at risk of stunting in Ogan Komering Ilir (96,266 households) and Lahat (70,922 households). Univariate and bivariate analyses revealed significant determinants of stunting risk, including: presence of reproductive-age couples, use of unsafe water sources, inadequate sanitation, families classified as 4T (too young, too old, too many, too close), and non-use of modern contraception. These findings highlight key factors that contribute to the risk of stunting in these regencies.